2012
DOI: 10.1159/000342206
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Gait Performance Detected by an Electronic Walkway System in 907 Older Adults of the Population-Based KORA-Age Study

Abstract: Background: Gait changes at older ages are a strong predictor of a decline in lower extremity functions. However, large population-based studies assessing gait parameters in various gait tasks are lacking. Objective: We investigated the relationship of age, the use of mobility aids and being fitted with an endoprosthesis with selected gait parameters, assessed in different walking tasks. Methods: In the population-based KORA-Age study, data from 907 men and women aged 65-91 years were obtained using the valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…33 A metronome was used to standardize the cadence of handlers' motion because of its accessibility and ease of use in practice. However, this approach limits the application of gait analysis in large clinical settings where multiple staff members are trained to collect data.…”
Section: Leash Side Differencementioning
confidence: 99%
“…33 A metronome was used to standardize the cadence of handlers' motion because of its accessibility and ease of use in practice. However, this approach limits the application of gait analysis in large clinical settings where multiple staff members are trained to collect data.…”
Section: Leash Side Differencementioning
confidence: 99%
“…Sensory, motor, biomechanics and cognitive aspects interacts providing functions such as postural control, gait and performance on multiple tasks, (3,4) which is relevant to daily life. Studies that assessed motor performance comparing healthy adults and old, shown age-related differences in several parameters, such as muscle strength, (5) balance, (6) gait performance, (7,8,9) cognition (1) and dual task performance. (10) What is not clear is if these differences remain evident when people are under stroke condition.…”
Section: Introductionmentioning
confidence: 99%
“…Besides gait velocity, older people tend to decrease dual-task-related cadence with increasing age [3, 44]. Higher cadence has been interpreted as an adaptive strategy to spend less time in the unstable single support phase or an alternative to increasing step length when walking faster [45].…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that patients with MCI in the IG adapted their gait pattern by performing more steps per minute, and therefore spending more time in a stable double support phase. In contrast, the CG adopted a gait pattern similar to that of more frail older people by decreasing cadence during the blinded treatment phase [44]. The normal range of mean cadence lies between 102 and 113 steps/min (age group 70–74) [46] which was better achieved by the IG than the CG.…”
Section: Discussionmentioning
confidence: 99%